Білім беру реформасындағы критериалды бағалау жəне оның ерекшеліктері - Рағатова, М.О.; Балыкбаева, Г.Ш.; Жумабаева, Ж.Н. (My University, 2016)
This article discusses the evaluation of educational reform. Authors focusing on the theoretical aspect of the criteria-based assessment trying to discover its features.
Keywords: reform; modernization; evaluation; criteria-based assessment; formative assessment; summative assessment